Peace Education Practices in Pre-Service Teacher Training Programs: and Analysis - Amin, Sufi; Jummani, N. B.; Mahmood, Sheikh Tariq; Raziq, Khan; Babar, Muhammad Ayoob Khan (European Scientific Journal, ESJ, 2016)
This study was designed to investigate peace education in pre-service teacher training programs in Khyber Pakhtunkhwa, Pakistan. The objectives of the present study to find out :( a) to examine prevailing practices of peace education in pre-service teacher training programs in Khyber Pakhtunkhwa Pakistan. (b) To evaluate the views of teacher Educators regarding the need of peace education in pre-service teacher training programs in Khyber Pakhtunkhwa Pakistan. (c) To suggest way of integrating peace education in pre-service teacher training programs in Khyber Pakhtunkhwa Pakistan. Using Survey method the data were collected through questionnaire from 245 teachers using simple random technique. A questionnaire was developed to investigate the opinions of the participants of the study. The data was analyzed by using the mean score, frequency and percentage.